Review of Time Series based Anomaly Detection Techniques - R, Raghavendran; BH, Chaitra (International Journal of Computer Sciences and Engineering, 2025)
Time series comprise a big portion of real-world data. Time series analysis is one of the most useful tools for researchers and developers. Anomaly detection is one of the key areas of focus in time series. This paper aims to provide a concise and cogent review of the existing research on the topic. In this paper, some widely accepted views and definitions of time series and anomalies are presented. Then, the various methods of anomaly detection in time series are presented, outlining their underlying mechanism, essential features, advantages and drawbacks. Finally, some common trends and observations are summarized, along with a look on the future directions of the research.